Library Management System - YAACOB, MUHAMMAD ESHAK AZRI; ABDUL JALIL, ROZITA (Applied Information Technology And Computer Science, 2026)
This project focuses on developing a Library Management System for the Parit Haji Siraj Library, which currently uses traditional, manual methods for managing its daily operations. These outdated methods slow down operations and create errors in managing library activities. As for the problem, this project introduces a Library Management System to improve and automate key library processes. The main objectives of this system are to reduce manual work, ensure accurate tracking of resources, and simplify essential tasks like book borrowing and returns. The system provides features like member registration, book catalogues, and overdue notifications, focusing on functionality and reliability. Developed using PHPMyAdmin for database management, along with web technologies, the system ensures secure data handling and operational consistency. The features are simple and practical, making them easy for library staff to use in daily operations. The results show that the system reduces errors in record-keeping, saves time, and increases operational efficiency. Staff can now handle tasks more effectively without depending on manual processes. In conclusion, the Parit Haji Siraj Library Management System provides a simple yet effective solution to improve library management. Future upgrades include digital library access and basic analytics to understand book circulation trends.